The effect of thermal cycling on the shear bond strength of porcelain/Ti-6Al-4V interfaces - Sendao, Isabel A.; Alves, Alexandra C.; Galo, Rodrigo [UNESP]; Toptan, Fatih; Silva, Filipe S.; Ariza, Edith (Elsevier B.V., 2015)
The aim of the study was to evaluate the effect of thermal cycling on the shear bond strength of the porcelain/Ti-6Al-4V interfaces prepared by two different processing routes and metallic surface conditions. Polished and SiO2 particle abraded Ti-6Al-4V alloy and Triceram bonder porcelain were used to produce the interfaces. Porcelain-to-metal specimens were processed by conventional furnace firing and hot pressing. Thermal cycling was performed in Fusayama's artificial saliva for 5000 cycles between 5 +/- 1 and 60 +/- 2 degrees C. After thermal cycling, shear bond tests were carried out by using a custom-made stainless steel apparatus. The results were analyzed using t-Student test and non-parametric Kruskal-Wallis test (p<0.01). Most of the polished-fired specimens were fractured during thermal cycling; thus, it was not possible to obtain the shear bond strength results for this group. Sandblasted-fired, polished-hot pressed, and sandblasted-hot pressed specimens presented the shear bond strength values of 76.2 +/- 15.9, 52.2 +/- 23.6, and 59.9 +/- 22.0 MPa, respectively. Statistical analysis indicated that thermal cycling affected the polished specimens processed by firing, whereas a significant difference was not observed on the other groups. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Dental porcelain; Hot pressing; Shear bond strength; Thermal cycling; Titanium alloy